2008
DOI: 10.1590/s1516-35982008001000014
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre genótipos e temperamento de novilhos Charolês x Nelore em confinamento

Abstract: RESUMO -Avaliou-se a influência da interação entre genótipos e do temperamento de bovinos sobre os ganhos diretos e indiretos para a produção de carne. Utilizaram-se 79 machos castrados com 19 a 20 meses de idade, divididos em oito grupos genéticos resultantes de cruzamentos Charolês × Nelore: 0, 25, 31, 38, 63, 69, 75 ou 100% Charolês. Os animais foram mantidos em confinamento e alimentados com uma dieta contendo 50% de volumoso e 50% de concentrado. O temperamento foi avaliado utilizando-se quatro metodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Even in feedlots systems, where daily contact occurs between animals and handlers, Silveira et al (2008) verified greater scores in reactivity (score = temperament, movement, and animal breathing) and flight distances for zebu cattle from the Nelore breed than for taurine cattle from the Charolais breed. While studying the carcasses of cattle from the Brahman, Bonsmara, and Beefmaster breeds, Mpakama et al (2014) confirmed that breed was the determining factor in the occurrence and severity of bruising.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Even in feedlots systems, where daily contact occurs between animals and handlers, Silveira et al (2008) verified greater scores in reactivity (score = temperament, movement, and animal breathing) and flight distances for zebu cattle from the Nelore breed than for taurine cattle from the Charolais breed. While studying the carcasses of cattle from the Brahman, Bonsmara, and Beefmaster breeds, Mpakama et al (2014) confirmed that breed was the determining factor in the occurrence and severity of bruising.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the animal's temperament is the determining factor for the number of bruises on the carcass (SILVEIRA et al, 2006(SILVEIRA et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Silveira et al (2008), os animais da espécie Bos indicus e seus cruzados apresentam maior reatividade em relação aos animais de sangue europeu, caracterizando-os como animais mais nervosos ou mais agitados. A reação dos animais também pode variar conforme o temperamento do indivíduo e o modo que são tratados durante a criação, animais que não são bem manejados e que possuem temperamento mais agitado demostram respostas mais intensas e duradouras quando expostos a situações de estresse (Paranhos & Magalhães, 2012;Ludtke et al, 2012).…”
Section: Resultsunclassified
“…A avaliação do temperamento de bovinos é uma ferramenta utilizada pela pesquisa para o aperfeiçoamento dos sistemas de criação e que tem consequências práticas e econômicas, portanto merece atenção dos produtores rurais (SILVEIRA et al, 2008).…”
Section: Introductionunclassified